1981
DOI: 10.1128/aac.19.5.798
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of gonorrhea: comparison of cefotaxime and penicillin

Abstract: Ninety-seven patients with 118 sites infected with Neisseria gonorrhoeae were treated with a single dose of either procaine penicillin G (4.8 x 10(6) U) or cefotoxime (1.0 g) intramuscularly. Only the penicillin group took 1 g of probenecid orally. The numbers of infected sites in each treatment group were as follows: penicillin-urethra, 37; rectum, 9; cervix, 8; and pharynx, 4; cefotaxime-urethra, 42; rectum, 9; cervix, 5; and pharynx, 4. The cure rates in each treatment group were 100%. No adverse reactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 8 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Twenty-five studies used intramuscular injection monotherapy that involved 6422 patients and compared the efficacy of 12 different drugs . Nineteen of these studies reported adverse reactions in 569 patients and the safety of 11 drugs was assessed [27][28][29][30][31][32][33][34][36][37][38][39][40][41][44][45][46]49,50]. Similarly, 19 studies focused on oral monotherapy [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70].…”
Section: Literature Search Process and Study Characteristicsmentioning
confidence: 99%
“…Twenty-five studies used intramuscular injection monotherapy that involved 6422 patients and compared the efficacy of 12 different drugs . Nineteen of these studies reported adverse reactions in 569 patients and the safety of 11 drugs was assessed [27][28][29][30][31][32][33][34][36][37][38][39][40][41][44][45][46]49,50]. Similarly, 19 studies focused on oral monotherapy [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70].…”
Section: Literature Search Process and Study Characteristicsmentioning
confidence: 99%
“…dose of cefotaxime was as effective as 4.8 x 10 6 U of procaine penicillin G in the treatment of uncomplicated gonorrhea. 119 A comparative study of cefotaxime versus clindamycin and gentamicin in the treatment of peritonitis (158 patients) and similar polymicrobial soft tissue surgical sepsis (91 patients) showed no significant difference between the two regimens. Infection was eliminated in 81 % of those treated with either antibiotic regimen, yet sepsis recurred in 6% of those treated with cefotaxime as compared to 13% of those given clindamycin/gentamicin.…”
Section: Comparative Clinical Trialsmentioning
confidence: 98%